Effect of biobased lipid surfactant on the rheology and morphology properties in alkalineâsurfactantâpolymer and crude oil system - Borhan, N. (Offshore Technology Conference, 2020)
Injection of chemicals in enhanced oil recovery (cEOR) such as alkaline (A), surfactant (S), and polymer (P) can increase the oil recovery by changing the properties of the injected fluid to make better interaction with oil in the reservoir. In this work, micellar fluid interactions were studied via microemulsion rheological behavior using naphthenic crude oil and stimulated brine contains ASP. The influence of water cut (WC), temperature, salt concentration, shear, and viscoelastic properties were studied using a chemical cocktail consist of ASP and Naphthenic Acid (NAs) crude oil with a formulated biobased chemical that contained synthesized compound. The rheological properties, when added biobased formulation labeled as surfactant S53 and S57 in the ASP-crude oil system, resulted in a different viscosity â viscous-like behavior of emulsion and microemulsion in varying quantity of synthetic brine and temperature. At a specific volume of brine, both emulsion and microemulsion from S53 and S57 undergo a shear-thinning phenomenon where it behaves like a non-newtonian micellar fluid, as when viscosity decreases with the increase of shear rate. This thixotropy characteristic is suitable to be applied at the injection well in which high shear rate condition requires lower viscosity to assist in injectivity. The fluid when it flows into the reservoir, the viscosity increases sweep residual oil in pore and oil film in pore throats. Overall in this paper will describe the rheology and its microscopic behavior of emulsion and microemulsion generated on the addition of S53 and S57 surfactants in determining the condition of cEOR micellar fluids application. Copyright 2020, Offshore Technology Conference